Konsep air sebagai asal usul kehidupan: Relevansi tinjauan ontologis dalam teori Thales, perspektif Al-quran dan sains - Prayogi, Rizky Bintang; Suta, Muhammad Zidane Ananda; Faisol, Faisol (Maliki Interdisciplinary Journal, 2025)
Water has become a conceptual meeting point between early Greek philosophy, the Qur’anic revelation, and modern science. This article examines water as the origin of life through an ontological approach that compares these three systems of knowledge. Using a conceptual analysis method and literature review, this study shows that water in Thales’ thought is the first principle (arche), in the Qur’an is a divine element of creation, and in modern science functions as the primary biological medium in the process of abiogenesis. The findings reveal a conceptual convergence despite differences in epistemological approaches. This article offers a philosophical synthesis that emphasizes the importance of integrating reason, revelation, and experimentation in understanding reality. The final conclusion affirms that water is not merely a chemical element, but an existential symbol that unites rationality, spirituality, and empiricism as a bridge to a more holistic understanding of life and existence.